POLA PENDAMPINGAN , PILIHAN ACARA DAN LAMA MENONTON TELEVISI PADA MURID BERPRESTASI DI KOTA SURAKARTA - Kurniawan, Donie Fadjar (Seni Media Rekam ISI Surakarta, 2010)
The objectives of this study are, first, to understand the pattern of guidance, second, to understand the choice of programme, and third, to understand duration of watching television to outstanding students at Surakarta. The data analysis shows as follows : the students watching television in a various ways; firstly, 56 % usually being together with their parents, no matter father or mother or both, 25 % being together with other family or relatives usually with siblings , and 19 % usually watching television by himself or herself. This kind of variations appear as the affect of pattern of guidance that is parents’ responsibility to be together while watching televsion. Secondly, from the choice programme, students have various of watching television, namely : 59% state that they have only several favorite television programmes. Next, 41% state that they have lots of favorite television programmes. Therefore, there is no statement showing no favorite television programmes. This kind of variation is also shown that 51% choose kids program as their favorite television programe. In queing: there are 13% to music, 12% to news programme, 11% film, 7% to sports, 6 % to comedy. Thirdly, from duration of watching, it is also shown that students watching in various condition namely: 59% like to watch television in unscheduled time, 25% like to watch everyday and 16% like to watch in sparetime (holiday). This kind of results also show that they take 3 until 4 hours daily to watch television during their sparetime (holiday), then 0 until 2 hours daily during their non sparetime (studying time).Key words: pattern of guidance, chocie of programe, duration of watching television, outstanding students.